2021
DOI: 10.21608/edj.2020.42708.1263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artificially Accelerated Ageing and Different Mouth Rinses on Color Stability of Veneered PEEK Crowns

Abstract: Statement of problem: Veneered polyether ether ketone (PEEK) is a recent alternative choice for fixed dental prostheses. There is a lack of data about the color stability of veneered CAD/CAM PEEK crowns using different veneering composite techniques. Purpose: To verify the effect of thermocycling and different mouth rinses on color stability of CAD/CAM composite versus conventional nanohybrid composite veneered PEEK crowns. Methods: Forty-two duplicated epoxy resin dies of prepared mandibular first molar to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Moreover, another explanation for the high stainability of Vita Enamic might be related to the effect of acids in wearing down the polymer content and leaving a rough surface of ceramic, which increased its staining liability [12,18] . The high Color change of PEEK (BioHPP) might also be due to the water absorption nature of the veneering composite material, as it is composed of BISGMA and TEGDMA, which shows high hydrophilicity [32] . This was in agreement with Hussein et al [33] and Badran et al [34] who proved the stainability of PEEK (BioHPP) layered with the crea.lign composite and they related their findings to the composite hydrophilicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, another explanation for the high stainability of Vita Enamic might be related to the effect of acids in wearing down the polymer content and leaving a rough surface of ceramic, which increased its staining liability [12,18] . The high Color change of PEEK (BioHPP) might also be due to the water absorption nature of the veneering composite material, as it is composed of BISGMA and TEGDMA, which shows high hydrophilicity [32] . This was in agreement with Hussein et al [33] and Badran et al [34] who proved the stainability of PEEK (BioHPP) layered with the crea.lign composite and they related their findings to the composite hydrophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the composition of the layering composite used (crea.lign) (Bredent, Germany) as it contained 50% nano-ceramic fillers with a 40 nm filler size that enhanced its aesthetic properties and stain resistance [32] . This was in agreement with Aydin et al [35] and Ziada and Beleidi [32] who revealed that the colour stability of composite is affected by the filler type and resin matrix The results of this study were in disagreement with Acar et al [37] who compared the effect of coffee staining on IPS e.max CAD, Vita Enamic, Lava Ultimate, and nanocomposites at different thicknesses (0.5 mm, 1 mm, and 1.2 mm). They found that Vita Enamic revealed a clinically perceivable but acceptable colour change following IPS e.max CAD, while nanocomposite showed an unacceptable colour change when stained with coffee.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was performed using a statistical power analysis software (G*Power v3.1.9.2, Heinrich-Heine-Universität, Düsseldorf, Germany). 18 A typodont mandibular first molar tooth was prepared to receive an all-ceramic crown by preparing a 1 mm chamfer finishing line, 1.5 mm occlusal reduction, 1 mm axial reduction, and 6°tapering angle. 18 It was then duplicated to create 20 dental epoxy resin dies.…”
Section: Methodsmentioning
confidence: 99%
“…18 A typodont mandibular first molar tooth was prepared to receive an all-ceramic crown by preparing a 1 mm chamfer finishing line, 1.5 mm occlusal reduction, 1 mm axial reduction, and 6°tapering angle. 18 It was then duplicated to create 20 dental epoxy resin dies. 19 Each prepared die was scanned using a 3D dental scanner (Identica Hybrid T500; MEDIT corp., Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation